Efficacy of system l amino acid transporter 1 inhibition as a therapeutic target in esophageal squamous cell carcinoma. Issue 10 (3rd October 2016) - Ohshima, Yasuhiro; Kaira, Kyoichi; Yamaguchi, Aiko; Oriuchi, Noboru; Tominaga, Hideyuki; Nagamori, Shushi; Kanai, Yoshikatsu; Yokobori, Takehiko; Miyazaki, Tatsuya; Asao, Takayuki; Tsushima, Yoshito; Kuwano, Hiroyuki; et al.
Abstract : Systeml amino acid transporter 1 (LAT1) is highly expressed in various types of human cancer, and contributes to cancer growth and survival. Recently, we have shown that LAT1 expression is closely related to the growth and aggressiveness of esophageal cancer, and is an independent marker of poor prognosis. However, it remains unclear whether LAT1 inhibition could suppress esophageal cancer growth. In this study, we investigated the tumor‐suppressive effects of the inhibition of LAT1. Both LAT1 and CD98, which covalently associates to LAT1 on the membrane, were expressed in human esophageal cancer cell lines KYSE30 and KYSE150. Quantitative PCR analysis showed that the expression of LAT1 was much higher than other subtypes of LAT. A selective inhibitor of LAT, 2‐aminobicyclo‐(2, 2, 1)‐heptane‐2‐carboxylic acid (BCH), suppressed cellular uptake ofl ‐ 14 C‐leucine and cell proliferation in a dose‐dependent manner. It also suppressed phosphorylation of mammalian target of rapamycin, 4E‐BP1, and p70S6K protein, and induced cell cycle arrest at G1 phase. These results suggest that suppression of both mammalian target of rapamycin signaling and cell cycle progression is involved in BCH‐induced growth inhibition. In tumor‐bearing mice, daily treatment with BCH significantly delayed tumor growth and decreased glucose metabolism, indicating that LAT1 inhibition potentially suppresses esophageal cancer growth in vivo . Thus, our results suggest that LAT1 inhibition could be a promising molecular target for the esophageal cancer therapy. Abstract : This paper shows the tumor suppressive effects by the inhibition of LAT1 in esophageal cancer. Inhibition of LAT1 with 2‐aminobicyclo‐(2, 2, 1)‐heptane‐2‐carboxylic acid (BCH) suppressed cell proliferation, mTOR signaling, and induced cell cycle arrest at G1 phase in esophageal cancer cells. Moreover, daily administration of BCH significantly delayed tumor growth and decreased glucose metabolism in tumor‐bearing mice, suggesting that LAT1 inhibition would be a promising molecular target for the therapy of esophageal cancer.